E-Commerce Transactions under Islamic Economic Law: Ensuring Shariah Compliance in Indonesian Digital Marketplaces - Wahdan; Widodo, Tri; Warmin; Muinah, Siti; Midiawati (Acitya Wisesa: Journal of Multidisciplinary Research, 2025)
The development of information technology has driven the growth of online buying and selling transactions through platforms such as Tokopedia, Shopee, and Bukalapak. This phenomenon opens economic opportunities while also posing challenges to the application of Islamic economic principles. This study employs a normative and descriptive qualitative approach to analyze the mechanism of digital transactions to ensure compliance with Shariah law, focusing on contracts (akad), transparency, consent (ridha), permissibility (al-ibahah), and accountability. The study’s findings show that digital contracts made through clicking “buy” and “pay” can be considered valid as long as they are clear, recorded, and agreed upon by both parties. Transparency of product information is a key principle to avoid gharar (excessive uncertainty) and ghish (deception), so the description, price, and condition of goods must be accurate. The principle of consent (ridha) is realized through options such as khiyar (choice), returns, and refunds as forms of consumer protection. Payment schemes must be free from riba (usury), maisir (gambling), and excessive gharar, with alternatives such as murabahah (cost-plus financing) and halal installments. Seller accountability is enforced through rating systems, reviews, and Shariah seller certification. The fatwa of the DSN-MUI (National Shariah Council-Indonesian Ulema Council) provides normative guidance for digital transactions, ensuring consumer protection and Shariah compliance. The implementation of these principles not only guarantees the validity of transactions but also enhances trust, consumer loyalty, and the sustainability of the Shariah e-commerce ecosystem in Indonesia.